Assessment of alternative feed sources with different levels of energy to protein ratio towards enhancement of layer and broiler performance - Abdulhameed, Mohammed Farooq (2019)
Formulation of poultry diets plays a role in decrease cost of the production. Poultry producers face a challenge to decrease cost of poultry products after competition between the human and animal on some ingredients is raised. There is a little information about using rice waste, meat and bone waste, and black soldier fly larvae meal as sources of energy and protein on layer and broiler performance. The objective of this study was to determine the effect of different levels of energy to protein ratio using rice waste as source of energy, and meat and bone waste as well as black soldier fly larvae meal as sources of protein in the diet on egg quality, productivity, and egg sensory characteristics of laying hens. Also, on growth performance, nutrient digestibility, microbial population, meat quality, gut histology, and sensory evaluation, and hepatic IGF-I and GHR mRNA gene expression of the broiler. In the first experiment, a total of 54 Arabic strain hens 36 weeks old were divided to three treatments, each 6 hens mixed with one cock. The energy to protein ratio of control treatment was 155, which is recommended by Nutrition Research Council. Low and high energy to protein ratio were used for second and third treatments, which were 144, and 170 respectively. Black soldier fly larvae were included in the diets at levels of 0, 5 and 1 % respectively. The results showed that a low energy to protein ratio diet increased hen day and hen house egg production (P<0.05), egg mass (P<0.001), feed conversion ratio (feed/kg egg) (P<0.01), sensory characteristics of eggs (P<0.05), and fertility rate(P<0.05). However, negative effects such as decrease of egg weight (P<0.001), and egg shell characteristics (P<0.05) accompanied with low energy protein ratio diet.In the second experiment, a total of 160 Cobb 500 one-day old chicks were divided randomly into four treatments. Conventional feed ingredients were formulated to form a control treatment. The normal energy to protein ratio of control treatment which is recommended in the guide of Cobb 500 was154 for the starter period and 167 for the finisher period. Rice waste, meat and bone waste as well as black soldier fly larvae meal were formulated to form the other three dietary treatments. The normal, low, and high energy to protein ratios of alternative feed diets were 154,143, and 166 for the starter period as well as 167, 155, and 177 for the finisher period respectively. The results showed that normal, low, and high levels of energy to protein ratio of alternative feed diets decreased feed intake (P<0.001), body weight gain (P<0.01), feed conversion ratio (P<0.001), carcass weight (P<0.01), crude protein digestibility (P<0.05), colour a* and b* values (P<0.001), villus height and crypt depth in duodenum (P<0.05), population of Lactobacillus spp (P<0.001) in ileum and cecum, population of Escherichia coli spp (P<0.001) in ileum, and population of Enterococcus spp (P<0.001) in cecum, but increased villus height and crypt depth (P<0.01) in jejunum, colour L* value of meat (P<0.05) compared with control diet. Normal and high energy to protein ratio of alternative feed diets decreased (P<0.05) ether extract digestibility, and population of Salmonella spp in ileum. Highest ash digestibility (P<0.001) and lowest cooking loss (P<0.01) values were observed in birds fed low energy to protein ratio. Low and high energy to protein ratio diets decreased population of Bifidobacterium spp in the cecum(P<0.05), pH of meat (P<0.05), and TBARS value (P<0.001) after 5 days of storage. Normal and low energy to protein ratio of alternative feed diets decreased (P<0.05) population of Enterococcus spp population in the ileum. In the third experiment, a total of 120 Cobb 500 one-day-old broiler chicks were divided randomly into four treatments. Conventional feed ingredients (corn, soy bean, and fish meal) were replaced with food waste (rice waste, meat and bone waste), and black soldier fly larvae at 10%, 30%, and 50%. The energy to protein ratio of all treatments was 154 for starter period and 166 for finisher period. The results showed that body weight gain (P<0.01), feed conversion ratio (P<0.05), the relative weight of abdominal fat (P<0.05), GHR and IGF1 mRNA gene concentrations (P<0.01) were increased when conventional feed ingredients were replaced with alternative feed ingredients at 30% and 50%. Lactobacillus spp population (P<0.01) in ileum and cecum, Escherichia coli population (P<0.001) in ileum, digestibility of (P<0.001) dry matter, crude protein, ether extract and ash, were increased when replacement of conventional feed ingredients with alternative feed ingredients at 10, 30, and 50%. However, Escherichia coli population were decreased (P<0.01) in cecum of birds fed diets of 10, 30, and 50% replacement. Enterococcus spp population was highest (P<0.01) in in ileum and cecum of birds fed diet containing 50% alternative feed ingredients. The present findings found that low energy to protein ratio diet increased hen day and hen house egg production of laying hens. Normal, low, and high energy to protein ratio of rice waste, larvae meal, and meat and bone waste of diet decreased growth performance and nutrient digestibility of broiler. Also, replacing of corn, soybean, fish meal with rice waste, larvae meal, and meat and bone waste up to 50% in the diet improved growth performance and nutrient digestibility of broiler.